Effect of graphite shape in vacuum-free diffusion bonding of nodular cast iron with gray cast iron - Özdemir, N; Aksoy, M; Orhan, N (Elsevier Science Sa, 2003)
In this study, the effect of graphite shape in vacuum-free diffusion bonding of nodular cast iron with gray cast iron was investigated. The material couples were diffusion bonded in an atmosphere controlled furnace under a pressure of 15 MPa and at the temperatures of 900, 950 and 1000 degreesC. The couples were held for 50, 100 and 150 min at each bonding temperature and then cooled to room temperature in the furnace. After the bond is formed, microstructural observations and hardness measurements were carried out in the bonding zone. From the results, it was observed that the shapes and surface areas of the graphites had an effect on the diffusion behaviors of the materials. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: diffusion bonding; nodular cast iron; gray cast iron; solid-state bonding